Penerapan Green Quality Function Deployment Produk Keripik Singkong - Mohammad Fuad Fauzul Mu'tamar; Raden Faridz; Aris Nurrahym (Universitas Trunojoyo Madura, 2020)
The attributes of the product may have an impact on the quality of the product for consumers. Depending on this, the product development of the industry needs greater attention to the materials and hygiene used and to reduce the environmental effect of cassava chip production. This study aims to obtain product attributes according to customer desires and proposed priority technical requirements to produce environmentally friendly cassava chips in accordance with the Green Quality Function Deployment method. The first phase is the identification of the customer requirement attributes with the FGD approach, and the results obtained are the nine customer requirement attributes. The highest weight of customer requirement attributes is the attributes of environmentally sustainable manufacturing processes valued at 1.34. There are 17 attributes for the development of HAJA cassava chips (UD. HAJA) in line with the customer expectations of interviews with three experts. The first priority is the formulation of seasoning raw materials of 8,67 per cent contribution value, the second priority being energy utilized with a contribution value of 8,59 per cent.